2016
DOI: 10.1089/thy.2016.0098
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Thyroid Hormone Levels Within the Normal and/or Subclinical Hyper- or Hypothyroid Range Do Not Affect Circulating Irisin Levels in Humans

Abstract: Changes in thyroid-axis hormone levels within the physiological or supraphysiological range do not affect circulating irisin levels in humans. Therefore, their metabolic effects are most likely independent of each other. Other regulators of irisin levels should be identified in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 48 publications
2
26
0
1
Order By: Relevance
“…Autonomous nodules are usually associated with less severe hyperthyroidism than, for example, Graves’ disease and present primarily as a subclinical hyperthyroidism at the moment of diagnosis. Subclinical thyroid function impairment is not associated with irisin level changes . According to the obtained data, it may be assumed that FNDC5 gene expression in thyroid tissue is not associated with the development of thyroid malignancy.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Autonomous nodules are usually associated with less severe hyperthyroidism than, for example, Graves’ disease and present primarily as a subclinical hyperthyroidism at the moment of diagnosis. Subclinical thyroid function impairment is not associated with irisin level changes . According to the obtained data, it may be assumed that FNDC5 gene expression in thyroid tissue is not associated with the development of thyroid malignancy.…”
Section: Discussionmentioning
confidence: 70%
“…Both studies confirm that short‐term disturbances in thyroid hormone concentrations do not lead to changes in irisin concentrations . Moreover, changes in thyroid hormone concentrations within the normal range or subclinical thyroid function impairments do not affect circulating irisin concentrations . Ateş et al demonstrated that circulating concentrations of irisin are elevated in hypothyroidism, and both obesity and irisin concentrations are independent risk factors for hypothyroidism .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Irisin was previously studied in patients with SCH (14,15), but only Stratigou and cols. evaluated serum irisin levels after being euthyroid with levothyroxine treatment (15).…”
Section: Adipokines In Subclinical Hypothyroidismmentioning
confidence: 99%
“…found decreased irisin levels in long-standing hypothyroidism and suggested that it might result from muscle damage due to prolonged myopathy and leakage of irisin from damaged muscle cells (7). Only two studies evaluated circulating irisin levels in SCH: Although irisin levels were similar between euthyroid and subclinical hypothyroid patients in one study (14), it was reported to be increased in the other study (15). Stratigou and cols.…”
Section: Adipokines In Subclinical Hypothyroidismmentioning
confidence: 99%